Edematous cutaneous loxoscelism associated with airway obstruction: a case report. - Alfaro-Sepúlveda, D.; González Fuentes, C.G. (European Journal of Pediatric Dermatology, 2021)
Loxoscelism is produced by the bite of Loxosceles spiders. There is in the literature a rare variant of cutaneous loxoscelism, mainly edematous, which is called edematous cutaneous loxoscelism (ECL). Here is reported the case of a 12-year-old girl, who presented ECLwith upper airway obstruction.